Interleukin-33 Levels are Up-Regulated in Women with Breast Cancer and Shown to be Associated with the Triple-Negative Type - Khalaf, Aseel F.; Ismaeel, Haneen M.; Khazaal, Ali Q.; Ad’hiah, Ali H. (Iraqi Journal of Science, 2024)
Breast cancer (BC) is a diverse disease with heterogeneous subgroups in pathophysiology and behavior. Recent advances in biomarker-based therapy may help improve treatment options for BC. Thus, this study aimed to assess the role of interleukin (IL)-31 and IL-33 as biomarkers associated with BC risk. Serum concentrations of IL-31 and IL-33 were quantified in women with BC (n = 77), women with benign breast lesion (BBL; n = 51), and healthy women (n = 75), using enzyme-linked immunosorbent assay kits. Compared with BBL or healthy women, IL-33 concentrations were significantly greater in BC patients and were associated with a 1.33-fold increased risk of disease and had excellent prognostic value in BC (area under the curve = 0.89). In addition, IL-33 expression was linked to triple-negative BC, distant metastasis, Tumor-Node-Metastasis (TNM) stage, status of estrogen and progesterone receptors, and human epidermal growth factor receptor 2. IL-31 concentrations showed no significant differences between BC, BBL, and healthy women, but were greater in patients with distant metastasis and those who were negative for estrogen and progesterone receptors. In conclusion, IL-33 and to a lesser extent IL-31 can be used as biomarkers associated with BC risk and to identify patients with a poor prognosis especially those with triple-negative BC. Furthermore, understanding the connection between IL-33 and BC progression may aid in the development of safe and effective therapy.